Association of Cumulative Remnant Cholesterol with Kidney Function Decline in Chinese Population: A Prospective Cohort Study - Lei Liu; Changfa Wang; Zhongyang Hu; Pingting Yang; Ying Li; Yufu Zhou; Saiqi Yang; Kui Chen; Shuwen Deng; Xiaoling Zhu; Xuelian Liu; Yaqin Wang (Kidney Diseases)
Introduction: There were limited data regarding the association between remnant cholesterol (RC), an emerging novel lipid marker, and chronic kidney disease (CKD). This study aimed to investigate the association of baseline and cumulative exposure of RC (cumRC) with kidney function decline (KFD) risk in the general population of China. Methods: Using data from the physical examination database in the Third Xiangya Hospital of Central South University (Changsha, China), 22,702 participants (age =18 years) without KFD, who underwent 3 consecutive annual health examinations between 2012 and 2015, were included. KFD was recorded during the interval between the third examination and the end of follow-up through 2020. Results: The cumRC was classified into 4 groups according to these cutoff values: 0.92, 1.33, and 1.99 (mmol/L). During a median follow-up of 3.17 years, 1,085 new KFD events were confirmed. Participants in the highest quartile of cumRC had 43% higher risk of KFD (hazard ratio, 1.43 [95% confidence interval, 1.16–1.77]), compared with the lowest quartile. Similarly, restricted cubic spline analysis showed a significant dose-response relationship between cumRC and the risk of KFD (P nonlinearity = 0.0314). However, baseline RC did not show any typical dose-dependent positive relationship with KFD development. In the discordance analysis, high baseline RC/low baseline low-density lipoprotein cholesterol (LDL-C) or high cumRC/low cumLDL-C were all associated with KFD in adjusted models. Conclusion: These data suggest a significant association between cumRC and risk of KFD independent of traditional CVD risk factors as well as the LDL-C level. Therefore, consistent RC monitoring should be given to individuals for early KFD prevention, especially in population with normal LDL-C levels who are often overlooked.